ANALYSIS OF THE CHANGE OF THE CONCEPT «FINANCIAL CRYPTOGRAPHY» ON THE BASIS OF 20 YEARS SUBJECTS OF THE INTERNATIONAL CONFERENCE «FINANCIAL CRYPTOGRAPHY AND DATA SECURITY» - Alexander A. Varfolomeev (Статистика и экономика)
The article discusses the concept of «financial cryptography», which appeared in 1997 in the eponymous conference title and used abroad to date along with concepts of «quantum cryptography», «post-quantumcryptography», «lightweight cryptography» and other. The focus is on changing the distinctive features of the concept of «financial cryptography» distinguishing it from the concept of the entire cryptography.